The diagnosis of a metastatic breast tumor from ovarian cancer by the succession of a p53 mutation: a case report - Ryutaro Mori; Manabu Futamura; Kasumi Morimitsu; Chiemi Saigo; Tatsuhiko Miyazaki; Kazuhiro Yoshida (World Journal of Surgical Oncology, 2017)
Abstract Background Metastatic breast tumors from other organs are very rare. We herein describe the case of a patient with a metastatic breast tumor due to ovarian cancer who was diagnosed by the succession of a p53 mutation. Case presentation The patient was a 59-year-old woman with sigmoid colon stenosis. Diagnostic imaging revealed a pelvic mass, multiple liver tumors, ascites, and multiple swollen para-aortic lymph nodes, suggesting an advanced ovarian tumor. Transverse loop colostomy and partial resection of the greater omentum was performed followed by six cycles of paclitaxel with carboplatin chemotherapy (TC therapy). Her cancer almost disappeared, with the exception of a small tumor in her pelvis. Simple hysterectomy with bilateral salpingo-oophorectomy was performed. Two years and 5 months after the second surgery, a mass was detected in her right breast and simple mastectomy was performed. A histological examination of the tumors from the first surgery revealed infiltrating papillary adenocarcinoma and the solid nest proliferation of atypical cells with comedo necrosis and psammoma bodies. The findings of an immunohistochemical analysis were as follows: cancer antigen 125 (CA125 (+)), cytokeratin 7 (CK7 (+)), cytokeratin 20 (CK20 (−)), p53 (+) and CDX2 (−), estrogen receptor (ER (slightly +)), progesterone receptor (PR (slightly +)), and human epidermal growth factor receptor 2 (HER2 (1+)). The breast tumors presented similar morphological features (ER (−), PR (−), HER2 (−), CA125 (+), CK7 (+), CK20 (−), p53 (+), mammaglobin (−), and GCDFP15 (−)), which were not characteristic of breast cancer. A direct sequencing analysis of p53 revealed a p.V173M mutation in exon 5 in both the breast tumor and the ovarian cancer. It was not detected in normal tissue, suggesting that the breast tumors were metastatic serous adenocarcinomas from ovarian cancer. Conclusions A direct sequencing mutation analysis of p53 was useful for distinguishing the primary tumor from the metastatic tumor. We should resect metastatic breast tumors to the extent that is possible because the prognosis of such patients is relatively good.